Sedimentology and geochemistry of thermokarst ponds in discontinuous permafrost, subarctic Quebec, Canada - Bouchard, Frédéric; Francus, Pierre; Pienitz, Reinhard; Laurion, Isabelle (Journal of Geophysical Research, 2011)
Thermokarst (thaw) ponds and lakes are distributed throughout arctic and subarctic regions; however their natural variability and temporal evolution recorded in the bottom sediments are poorly understood. This paper presents a multiproxy study conducted in a subarctic site with many thermokarst ponds near Kuujjuarapik‐Whapmagoostui, on the eastern shore of Hudson Bay. Sedimentological, geochemical and chronological analyses have been performed on short sediment cores (10–20 cm) retrieved from limnologically contrasted ponds. Analyses revealed two distinct sedimentary facies, from bottom to top: 1) massive marine silts and clays deposited during postglacial Tyrrell Sea transgression (ca. 8000 to 6000 cal yr BP), subsequently emerged by glacio‐isostatic rebound and more recently (ca. 1500 to 400 cal yr BP) affected by permafrost inception and growth; 2) laminated organic‐rich lacustrine muds deposited since permafrost thawing and subsidence, i.e., since thermokarst pond inception (the last centuries). Despite displaying strikingly different water colors, the study ponds showed similar long‐term developmental patterns regarding their physico‐chemical properties (as recorded in the sediments), such as decreasing mineral grain size (from silts to clays), decreasing major chemical element concentrations, increasing organic matter content, and decreasing bottom water oxygen concentrations (from well‐oxygenated to anoxic/hypoxic conditions). Key Points Thermokarst ponds are widespread in subarctic Quebec (Canada) but poorly studied A multiproxy study was conducted to explore their sedimentology and geochemistry Results suggest a link between their age and their limnological properties